2012
DOI: 10.1186/1755-8794-5-26
|View full text |Cite
|
Sign up to set email alerts
|

Screening significantly hypermethylated genes in fetal tissues compared with maternal blood using a methylated-CpG island recovery assay-based microarray

Abstract: Background The noninvasive prenatal diagnosis procedures that are currently used to detect genetic diseases do not achieve desirable levels of sensitivity and specificity. Recently, fetal methylated DNA biomarkers in maternal peripheral blood have been explored for the noninvasive prenatal detection of genetic disorders. However, such efforts have covered only chromosomal aneuploidy, and fetal methylated DNA biomarkers in maternal whole blood for detecting single-gene diseases remain to be discover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 31 publications
(33 reference statements)
2
5
0
Order By: Relevance
“…Based on the 450K array analysis and independent validation by bisulfite genomic sequencing, priority was given for 27 CpG units located in 10 regions, with multiple differential methylated CpG sites overlapped with at least two MSRE recognizing sites and one polymorphic SNP, within a short stretch of DNA. Notably, three regions ( RASSF1A , SKI , and VAPA‐APCDD1 ) were previously described, thus emphasizing the robustness of our data. As a preliminary study, we selected three target regions involved in PSMB8 , SKI , and , detecting their presence in plasma samples before and after MRSE digestion.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Based on the 450K array analysis and independent validation by bisulfite genomic sequencing, priority was given for 27 CpG units located in 10 regions, with multiple differential methylated CpG sites overlapped with at least two MSRE recognizing sites and one polymorphic SNP, within a short stretch of DNA. Notably, three regions ( RASSF1A , SKI , and VAPA‐APCDD1 ) were previously described, thus emphasizing the robustness of our data. As a preliminary study, we selected three target regions involved in PSMB8 , SKI , and , detecting their presence in plasma samples before and after MRSE digestion.…”
Section: Discussionsupporting
confidence: 73%
“…Until now, a number of studies have reported placental epigenetic biomarkers on Chromosomes 13, 18, and 21, which are frequently found to be aneuploid in live births. However, only few investigations have focused on the candidate epigenetic targets on other chromosomes, neither of their potential applications besides fetal aneuploid diagnosis. Here, the quantitative Illumina BeadChip technique enables us to detect selected CpG sites in a genome‐wide basis at a single‐nucleotide resolution in virtually all genes, demonstrating the comprehensive differential methylation patterns in fetal placenta versus maternal blood cells.…”
Section: Discussionmentioning
confidence: 99%
“…The methylation status of the selected DMRs was also compared with previous studies that utilized methylation differences between fetal and maternal tissue for the identification of fetalspecific biomarkers. Common DMRs were found between our approach and DMRs identified using bisulphite conversion, methylationsensitive restriction digestion and microarrays (Old et al , 2007; Chim et al , 2008; Chu et al , 2009; Bunce et al , 2012; Yin et al , 2012; Lun et al , 2013; Hatt et al , 2015). More concordant results were observed between our study and DMRs identified using MeDIP approaches (Papageorgiou et al , 2009; Ioannides et al , 2014; Xiang et al , 2014).…”
Section: Resultsmentioning
confidence: 70%
“…[13][14][15] Considerable effort has also been devoted to investigate mutational events that could explain cancer-related aberrant methylation through their effect on the epigenetic machinery. 16,17 Recently, the development of clinically relevant diagnostic tests for cancer based on methylation biomarkers measured in blood, urine, and other body fluids [18][19][20][21][22] have provided a glimpse into the biomedical applications that may become mainstream in the near future. 23 DNA methylation experiments performed by individual laboratories provide evidence for the identification of shared signatures of differential methylation that can separate tumors from normal controls.…”
Section: Introductionmentioning
confidence: 99%